Long‐term follow up of peginterferon‐α‐2a treatment of hepatitis B e‐antigen (HBeAg) positive and HBeAg negative chronic hepatitis B patients in phase II and III studies. Issue 10 (18th January 2016) - Okanoue, Takeshi; Shima, Toshihide; Hasebe, Chitomi; Karino, Yoshiyasu; Imazeki, Fumio; Kumada, Takashi; Minami, Masahito; Imai, Yasuharu; Yoshihara, Harumasa; Mita, Eiji; Morikawa, Teruhisa; Nishiguchi, Shuhei; et al.
Abstract : Aim: We analyzed the 5‐year post‐treatment response to peginterferon α‐2a (PEG IFN‐α‐2a) in hepatitis B e‐antigen (HBeAg) positive and negative chronic hepatitis B patients. Methods: One hundred and thirty‐seven chronic hepatitis B (CHB) patients receiving 90 μg or 180 μg of PEG IFN‐α‐2a for 24 or 48 weeks in phase II or III studies were enrolled in the study, including 100 HBeAg positive patients and 37 HBeAg negative patients; 121 patients (88.4%) had genotype C. Results: Of the 137 patients, 94 received additional antiviral therapy because of viral reactivation and 43 did not receive any additional antiviral treatment during follow up. Five years upon PEG IFN‐α‐2a treatment, 32 patients (23.4%) who did not receive any additional antiviral agent after PEG IFN‐α‐2a therapy achieved a good response (normal serum alanine aminotransferase, low‐level hepatitis B virus [HBV] DNA, and HBeAg negativity). Female sex and low HBV DNA levels by the end of treatment were independently associated with favorable 5‐year post‐treatment responses. Forty‐eight‐week administration of PEG IFN‐α‐2a showed a better response (26.4%) than 24‐week administration (18.0%). Six patients (4.3%), four males and two females, cleared hepatitis B surface antigen (HBsAg) during the 5‐year follow‐up period. Conclusion: The 48‐week administration of PEG IFN‐α‐2a achieved better biochemical and virological responses than the 24‐week administration, particularly in younger females. The 5‐year post‐treatment response rate was 23.4%; however, more than two‐thirds of the patients received additional antiviral therapy because of viral reactivation after PEG IFN‐α‐2a treatment. HBsAg clearance was noted in six patients (4.3%). PEG IFN‐α‐2a is effective in young female patients.